Communal management of drinking water and municipal technical assistance in rural areas. Experience in the district of San Marcos, Ancash - Escate Cavero, Juan (2012)
This study addresses the communal management of the drinking water service and municipal technical assistance, based on three rural communities located in the district of San Marcos during the period 2006 - 2009. The study suggests that the municipality - communal organization relation enhances the sustainability of the drinking water service because it reinforces the local management dynamic, legitimizes local authorities and fosters communal membership